La production de l’énergie électrique dans les zones isolées Le cas du Grand Sud de l’Algérie: Electric power generation in the isolated areas The case of Great South of Algeria - Dahmani Souria; Mouhoubi Aissa; Kremia Walid; Mouhoubi Moussa (Journal of North African Economies, 2025)
The purpose of this study is to verify the economic profitability of a broad integration of renewable energies in the electricity production sites of the South Isolated Grids of Algeria. Production ensured by diesel engines and small power gas turbine units. Unable to be connected to the national interconnected grid, the coverage of the local demand for electricity in these regions is very expensive and increases dramatically with distance and isolation. Guaranteeing an energy mix is an objective imposed on Algeria to make conventional power plants profitable and reduce fuel consumption. The hybridization of diesel plants with photovoltaic solar power plants contributed to reducing the consumption of fossil fuels and to ensure an intergenerational saving of resources.